シン コガタ セツジョウシャ ノ シケン ケッカ ニ ツイテ - 喜納, 淳; キノウ, アツシ; 細谷, 昌之; ホソヤ, マサユキ; 竹内, 貞男; タケウチ, サダオ; 金内, 賢; カナウチ, マモル; Kinou, Atsushi; Hosoya, Masayuki; Takeuchi, Sadao; Kaneuchi, Mamoru (1988)
P(論文) 昭和基地ならびに沿岸地域で使用する小型雪上車を国立極地研究所設営専門委員会小型雪上車設計作業委員会が開発した。この雪上車は, 主として氷上で行動することから, 軽量化を図ることを開発の条件の一つとした。このため, 動力伝達システムには全油圧駆動方式を採用した。この方式は, 日本の南極観測では始めてのことであるので, 低温下での始動試験, 始動に用いるバッテリーの持続試験を行った。全油圧駆動方式に伴う車両の操縦上の問題について試験を行い, 必要な改善策を講じた。また, 車両のピッチングを減少するために, 懸架装置についての試験も行い, 必要な改善を行った。完成した新小型雪上車は第28次観測隊により昭和基地に搬入され使用されている。 A new small snow vehicle for operating at Syowa Station and vicinities was developed by the working group on snow vehicle, the Committee on Antarctic Logistics, National Institute of Polar Research. Attention was paid to make the vehicle light weight because it was expected to be driven on the sea ice. To fulfill this objective, the hydrostatic transmission system was adopted for the mechanical power train. Since the introduction of the snow vehicle equipped with the hydrostatic transmission system was the first experience for the Japanese Antarctic Research Expedition, fundamental tests of this system such as the starting of engine and the duration of battery power under low temperatures expected in the Antarctic, were conducted. Tests were made also to examine the steerbility of the vehicle with the hydrostatic transmisstion system, and required improvements were made. The shock-absorbing properties of the suspension were tested in order to reduce the pitching motion of vehicle. The first small size snow vehicle which was improved based on the test results has been used in good condition in the Syowa Station area since the 1987 summer. departmental bulletin paper